2019
DOI: 10.24875/acme.m19000003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the global longitudinal strain and segmental strain of the right ventricle with two-dimensional speckle-tracking echocardiography with elevation of the legs

Abstract: Evaluación de la deformación longitudinal global y segmentaria del ventrículo derecho con ecocardiografía bidimensional speckle-tracking con la elevación de las piernas

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
1
2
0
2
Order By: Relevance
“…Our study has several limitations: first, it is possible that infusion of larger volume would have led to significant changes in 2D-STE parameters or in 2D conventional parameters. However, our results were comparable to those of the study using passive leg raising, which is a dynamic manoeuvre allowing to mobilize 300 mL of blood in order to induce a change in preload [ 11 , 15 ]. Moreover, different shapes, body compositions, and basal circulating states of the subjects may have influenced FC results.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our study has several limitations: first, it is possible that infusion of larger volume would have led to significant changes in 2D-STE parameters or in 2D conventional parameters. However, our results were comparable to those of the study using passive leg raising, which is a dynamic manoeuvre allowing to mobilize 300 mL of blood in order to induce a change in preload [ 11 , 15 ]. Moreover, different shapes, body compositions, and basal circulating states of the subjects may have influenced FC results.…”
Section: Discussionsupporting
confidence: 82%
“…To our knowledge, there are few data on RV preload dependency of 2D-STE parameters in healthy volunteers. Garcia-Lopez et al [ 15 ] reported that strain analysis was reproducible (ICC 0.773) and sensitive to detect differences in RV4CLS after a passive leg-raising manoeuvre in 31 healthy volunteers. However, the strain analysis was not performed in the RV apical view but by with analysis of the six segments in a classical four-chamber view.…”
Section: Discussionmentioning
confidence: 99%
“…Author details 1 Hospital General de Ticomán, Secretaría de Salud Ciudad de México, Mexico City, Mexico. 2 Escuela Nacional de Medicina y Homeopatía, Instituto Politécnico Nacional, Mexico City, Mexico. 3 Hospital General Xoco, Secretaría de Salud Ciudad de México, Mexico City, Mexico.…”
Section: Author's Informationunclassified
“…The more negative strain value the better myofibril shortening. In the clinical practice, longitudinal strain (deformation in the base-apex direction) is useful for evaluating left ventricle contractile function [2]. Some cardiometabolic conditions like type 2 Diabetes Mellitus (t2DM), insulin resistance or obesity may induce cardiac myofibrillary dysfunction [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Атеросклеротичною бляшкою вважають локальну структуру, яка виступає в просвіт артерії не менше ніж на 0,5 мм, або збільшення ТКІМ на 50% порівняно з відповідним показником в навколишньому оточенні, або ТКІМ>1,5 мм [20].…”
Section: лекціїunclassified